Toward slow archives - Christen, Kimberly; Anderson, Jane (Archival science, 2019)
This article examines the structures, practices, and processes of collection, cataloging, and curation to expose where current cultural authority is placed, valued, and organized within archival workflows. The long arc of collecting is not just rooted in colonial paradigms; it relies on and continually remakes those structures of injustice through the seemingly benign practices and processes of the profession. Our emphasis is on one mode of decolonizing processes that insist on a different temporal framework: the slow archives. Slowing down creates a necessary space for emphasizing how knowledge is produced, circulated, and exchanged through a series of relationships. Slowing down is about focusing differently, listening carefully, and acting ethically. It opens the possibility of seeing the intricate web of relationships formed and forged through attention to collaborative curation processes that do not default to normative structures of attribution, access, or scale.